Analisis Strategi Pemasaran Agroindustri Opak di Desa Tuntungan I Kecamatan Pancur Batu Kabupaten Deli Serdang - Iffan Harahap; Dian Habibi; Abdul Rizal (Universitas Medan Area, 2020)
The agricultural sector in Indonesia still has many opportunities and has bright prospects that have not yet been explored. In the agribusiness system, agro-industry is one of the subsystems which together with other subsystems form agribusiness. Cassava is an important source of carbohydrate in the world. In Indonesia, cassava is the number three staple food after rice and corn. The purpose of this research is to determine the Opak Industry Agro Marketing Strategy in Tuntungan I Village, Pancur Batu District, Deli Serdang Regency using survey methods, while data analysis is done using descriptive methods and SWOT analysis. The results of the study show that the strategy obtained is the SO (Strengths-Opportunites) strategy, which is to use the power to take advantage of existing opportunities by increasing production by optimizing the availability of raw materials to increase product marketing in the market. (S1, O1) Optimize market share from outside the region by utilizing raw material prices (S2, O2) Empowering family workers in utilizing supporting facilities and infrastructure in the production process (S1, S3-O3) Utilizing the selling price of products to improve local food products became a trend of the community with a market share of products outside the Region (S4.02, O4).